CryoEM: a crystals to single particles round-trip. (October 2019) - Hebert, Hans
Highlights: Electron crystallography from 2D- or thin 3D crystals may provide structural information which is difficult to obtain with other methods. 3D maps are related to the Coulomb potential rather than the electron density as in X-ray crystallography. High resolution can provide pieces of information that are essential for explaining chemical properties. Abstract : In the era of intense and steadily increasing attention to cryo electron microscopy (cryoEM) as a powerful tool in structural biology, particularly with regard to randomly oriented biological macromolecules, studies of 2D and small 3D crystals using cryoEM provide added value for addressing-specific questions. Size and shape demands are not as restrictive as for single particle specimens. Crystallization may stabilize whole or partly flexible molecules. Resolutions beyond 2 Å, for 3D crystals even sub-Ångström structures, can be obtained allowing studies of chemical properties in detail. The electron dose can be kept low and reduce radiation damage for sensitive specimens. In contrast to X-ray crystallography, scattering of electrons will be directly related to the Coulomb potential and thus give information about charge distribution in biomolecules.